Analisis Pengaruh Beban Gempa pada Gedung Tujuh Lantai Menggunakan Metode Statik Ekuivalen (Studi Kasus Rumah Sakit Ibu dan Anak Hermina Lampung) - Wafi, Alvino; Isneini, Mohd; Husni, Hasti Riakara (Universitas Lampung, 2021)
Earthquake is one of the natural disasters that often occurs in Indonesia. One of the effects of earthquake natural disasters is that it can damage building structures. Therefore, the building to be built should take into account the effect of the earthquake load. Planning for a safe multi-storey building must minimize the risk of casualties, especially for health building facilities where there is a lot of human activity. SNI 1726: 2019 is the latest regulation governing the planning procedures for earthquake resistant buildings. In this research, structural modeling software is used to facilitate the analysis to be carried out. The expected results of this study are (1) Comparison of the value of the force in the RSIA Hermina building structure without earthquake loads and with earthquake loads (2) The ability of the RSIA Hermina building structure to withstand the internal forces generated from the analysis using the equivalent static method. From the results of this study, it was found that the increase in moment and latitude values in the beam and column was 2 to 20 times. Meanwhile, the floor slab structure does not experience the impact due to earthquake loads.